2016
DOI: 10.1051/e3sconf/20160909003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on the measurement of the apparent contact angle in sand of varying wettability under air-dried conditions

Abstract: Abstract. Changes in the wettability of soil are known to affect several processes such as infiltration and the shear strength of soil. In this study, the wettability of a medium to fine sand was chemically modified by using different concentrations of dimethyldichlorosilane (DMDCS). The sessile drop method (SDM) was used for the assessment of wettability of hydrophobised Leighton Buzzard Sand (LBS). The results demonstrate that beyond a concentration of 2 g per kg of LBS, the finer fraction had its apparent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…For larger grain sizes, the droplet begins to penetrate the surface structure, resulting in lower droplet mobility, due to more solid surface contact. This is consistent with observations of other soils (de Jonge et al, 1999; Doerr et al, 1996; Saulick et al, 2016) and synthetically created textured hydrophobic surfaces (Erbil et al, 2003; McHale et al, 2005; Öner & McCarthy, 2000; Yeh, Chen, & Chang, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For larger grain sizes, the droplet begins to penetrate the surface structure, resulting in lower droplet mobility, due to more solid surface contact. This is consistent with observations of other soils (de Jonge et al, 1999; Doerr et al, 1996; Saulick et al, 2016) and synthetically created textured hydrophobic surfaces (Erbil et al, 2003; McHale et al, 2005; Öner & McCarthy, 2000; Yeh, Chen, & Chang, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…This supports the earlier works of McHale, Shirtcliffe, Newton, and Pyatt (2007), who showed that a Cassie‐Baxter wetting regime could exist in water‐repellent soils, and where this is extreme, has the potential to create superhydrophobicity. For soils where studies have used either real soils consisting of a mixture of different grain sizes (Bachmann et al, 2006; Leelamanie, Karube, & Yoshida, 2008) or where grain fractions as small as clay or clay aggregates were not isolated in grain size‐dependent contact angle studies (Saulick, Lourenço, and Baudet (2016), typical values of contact angles are reported in the range of 100–130°. Higher contact angles have been recorded in model soils; for example, Bachmann et al (2013) measured contact angles of 140° using a small‐scale contact angle measurement technique, and Ng and Lourenço (2016) report angles up to 143° for silane‐treated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Each oil drop created in the pendant-drop system was given a stabilization time of 30 min, and the contact angle was tracked during this period, without finding any significant changes in the measured value. Dimethyldichlorosilane produces a hydrophobic behavior on treated surfaces, due to the absorption process on the solid surface [53,54]. Contact angle provided information to verify the surface changes to a hydrophobic response, confirming an oleophilic behavior and therefore the wettability alteration within the three components system.…”
Section: Interfacial Tension and Contact Anglementioning
confidence: 80%
“…14 Literature studies on contact angle measurements of the LS indicated that the amorphous behavior negates the lattice energy limitations seen in crystals while the smaller size of particles had higher wetting and faster diffusion of water into the solid. 15 …”
Section: Resultsmentioning
confidence: 99%